2021
DOI: 10.3390/en14061768
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Slaughterhouse Wastes to Solid Fuel Using Hydrothermal Carbonization

Abstract: In this study, cattle and pig slaughterhouse wastes (SHWs) were hydrothermally carbonized at 150–300 °C, and the properties of SHW-derived hydrochar were evaluated for its use as a solid fuel. The results demonstrated that increasing the hydrothermal carbonization (HTC) treatment temperature improved the energy-related properties (i.e., fuel ratio, higher heating value, and coalification degree) of both the cattle and pig SHW-derived hydrochars. However, the improvements of cattle SHW-derived hydrochars were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The energy potential of raw feedstock was 4.541 MJ/kg and the total gross energy recovery of the biochar was decreased (81.2 to 75.6%) with an increase in the temperature whereas the total gross energy recovery of 4.318 MJ/kg was obtained at 180 °C which maximized gross energy recovery efficiency by 95.1%. Lee et al [146] performed the HTC of cattle and pig slaughterhouse waste in a batch scale type laboratory reactor at different temperatures (150, 200, 250, and 300 °C). It is known that the carbon content is closely associated with the energy capacity of combustible material and it is observed that the carbon content of hydrochar is increased with an increase in the hydrothermal carbonization temperature.…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
“…The energy potential of raw feedstock was 4.541 MJ/kg and the total gross energy recovery of the biochar was decreased (81.2 to 75.6%) with an increase in the temperature whereas the total gross energy recovery of 4.318 MJ/kg was obtained at 180 °C which maximized gross energy recovery efficiency by 95.1%. Lee et al [146] performed the HTC of cattle and pig slaughterhouse waste in a batch scale type laboratory reactor at different temperatures (150, 200, 250, and 300 °C). It is known that the carbon content is closely associated with the energy capacity of combustible material and it is observed that the carbon content of hydrochar is increased with an increase in the hydrothermal carbonization temperature.…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
“…The red meat and poultry industry is probably one of the fastest-growing meat industries [3]. The increased consumption of meat and meat-related products has contributed to the expansion of the red meat and poultry slaughterhouse industry, and thus to an increase in the number of slaughtering derivatives generated through slaughterhouses [4].…”
Section: Opsommingmentioning
confidence: 99%
“…'Slaughterhouse waste' refers to the products that remain after the production of the principal commodity in slaughterhouses (the meat), and essentially comprises inedible offal and fats [4]. However, terms such as 'slaughterhouse waste' and related terms such as 'offal', 'by-products', and 'co-products' are sometimes used interchangeably [5].…”
Section: Opsommingmentioning
confidence: 99%
“…These approaches either require a significant amount of energy and produce air pollutants or necessitate a large land area for implementation. Given its high organic content, SHW poses challenges for conventional treatment, necessitating careful planning to manage animal-derived diseases, safeguard public health, and minimize its environmental impact [4].…”
Section: Introductionmentioning
confidence: 99%